Interações parasito-hospedeiro em anuros de um enclave de floresta tropical altitudinal do semiárido brasileiro - Oliveira, Cicero Ricardo de (2023)
Environmental heterogeneity has been a factor often used to explain the different species richness around the world, since the distribution, diversity and richness of species can be determined by the structure of the environment. In addition, more diverse environments harbour higher species richness. Another aspect that may influence this is the altitude gradient, a limiting factor for a set of biotic and abiotic factors that influence the structure of communities. This has been the focus of many studies in ecology, especially of amphibians, animals strictly related to environmental conditions, making these hosts an excellent model to assess patterns in the structure of parasite communities. Many processes are reported to influence the structure of helminth communities in amphibians, including host size, genus, diet, site of infection, species and behaviour, leading parasite richness to vary depending on environmental conditions and the way species respond to biotic factors. The Caatinga domain is known to have a high degree of herpetofauna endemism, especially in wet forest enclaves, known as “brejos-de-altitude”. Considering these aspects, we will use the Environmental Protection Area of Serra de Maranguape due to the diversity of microenvironments, to carry out the study. Thus, we distributed nine sampling points along three altitude gradients and collected anurans during the rainy season, by active search. Therefore, in the present study, we aimed to (A) describe the composition of endoparasites associated with anurans from an altitudinal forest enclave in Northeast Brazil, the Serra de Maranguape; (B) test the influence of microhabitat use on endoparasite abundance and richness; (C) test the hypothesis that larger frogs tend to be more parasitized; (D) test the influence of habitat heterogeneity and altitudinal gradient on endoparasite abundance and richness; (E) test the phylogenetic relationship between hosts and parasites; (F) test the hypothesis that parasites are distributed following their hosts without influence of environmental variation; and (G) obtain information on the host-parasite relationship of the helminth fauna of the critically endangered species Adelophryne maranguapensis.